Recurrent bacteremia with a hypermucoviscous Escherichia coli isolated from a patient with perihilar cholangiocarcinoma: insights from a comprehensive genome-based analysis - Bernd Neumann; Norman Lippmann; Sebastian Wendt; Thomas Karlas; Christoph Lübbert; Guido Werner; Yvonne Pfeifer; Christopher F. Schuster (BMC, 2022)
Abstract Background Escherichia coli (E. coli) is a common human pathogen, responsible for a broad spectrum of infections. Sites of infection can vary, but the hepato-biliary system is of particular concern due to the infection-associated formation of gallstones and the spread of pathogens from the bile ducts into the bloodstream. Case presentation The presented case is striking, as the detected isolate showed a positive string test. This hypermucoviscous phenotype is atypical for E. coli and a particular feature of hypervirulent Klebsiella pneumoniae (K. pneumoniae) variants. Objectives To provide new insights into the genomic background of an E. coli strain with an unusual hypermucoviscous phenotype using hybrid short- and long-read sequencing approaches. Results Complete hybrid assemblies of the E. coli genome and plasmids were done and used for genome based typing. Isolate 537-20 was assigned to the multilocus sequence type ST88 and serotype O8:H4. The strain showed a close relationship to avian pathogenic strains. Analysis of the chromosome and plasmids revealed the presence of several virulence factors, such as the Conserved Virulence Plasmidic (CVP) region on plasmid 537-20_1, including several iron acquisition genes (sitABCD, iroABCDEN, iucABCD, hbd) and the iutA gene encoding the receptor of the siderophore aerobactin. The hypermucoviscous phenotype could be caused by encapsulation of putative K. pneumoniae origin. Conclusions Hybrid sequencing enabled detailed genomic characterization of the hypermucoviscous E. coli strain, revealing virulence factors that have their putative origin in K. pneumoniae.